Globalisasi: IMF, Bank Dunia dan Amandemen Pasal 33 - Hudiyanto - (Universitas Islam Indonesia, 2003)
The following article investigates theglobalization as an actual topic that rises in recent ten years. Talking about the globalization in Indonesia intends to conduct amendment of article 33 of The Constitution 1945. The majority of the remember of Indonesian representatives state that refers to globalization, the article regarding economy must be abrogated. The author of this article tries to describe the substance between IMFand World Bank in actualizing the spirit of globalization bycarrying out amendment of the constitution that closed relating to Indonesia micro-economy development. There is a crucial problem when the amendment article 33 of the Indonesian Constitution will be applied.